Novel calcaneal plate versus traditional philos plate for treating split fractures of humeral greater tuberosity - Wang, Fei; Niu, Xiaohui; Xia, Haibo; Liang, Wei; Hu, Zhen; Lan, Jun (Frontiers in Surgery, 2024)
Purpose: To compare the effect of two internal fixation methods of calcaneal plate fixation and Philos plate fixation in treating split fractures of humeral greater tuberosity.A total of 37 patients with split fractures of humeral greater tuberosity were retrospectively analyzed from September 2016 to April 2021.Enrolled patients were divided into Group A (calcaneal anatomical locking plates), and Group B (Proximal Humeral Internal Locking System (PHILOS)). The demographics, injury-related variables, surgery-related variables, Constant-Murley score, and postoperative complication between the two groups were compared.Results: There were 16 in Group A and 21 in Group B. Fracture union was achieved in all patients, with an average of 11.9 months. The mean length of incision was significantly different between groups (Group A, 6.16 ± 1.07 cm; Group B, 9.09 ± 1.30 cm, p < 0.05). Significant difference was observed by comparing bleeding loss between Group A and Group B (Group A, 45.41 ± 11.19 ml; Group B,106.06 ± 11.12 ml, p < 0.05). After 6 months of treatment, the average Constant-Murley score of Group A was significantly higher than that of Group B (p < 0.05). In terms of operation, no significant difference was observed between groups. In addition, two patients had shoulder impingement syndrome in Group B, and none in Group A.Calcaneal anatomical locking plate fixation is superior to Philos plate fixation in surgical trauma and bleeding loss. Our study provides an alternative technique for treating split fractures of humeral greater tuberosity.